Mitochondrial quality control in the brain: The physiological and pathological roles - Shen, Xurui; Sun, Peixin; Zhang, Hao; Yang, Hanting (Frontiers in Neuroscience, 2022)
The human brain has high energetic expenses and consumes over 20% of total oxygen metabolism. Abnormal brain energy homeostasis leads to various brain diseases. Among multiple factors that contribute to these diseases, mitochondrial dysfunction is one of the most common causes. Maintenance of mitochondrial integrity and functionality is of pivotal importance to brain energy generation. Mitochondrial quality control (MQC), employing the coordination of multiple mechanisms, is evolved to overcome many mitochondrial defects. Thus, not surprisingly, aberrant mitochondrial quality control results in a wide range of brain disorders. Targeting MQC to preserve and restore mitochondrial function has emerged as a promising therapeutic strategy for the prevention and treatment of brain diseases. Here, we set out to summarize the current understanding of mitochondrial quality control in brain homeostasis. We also evaluate potential pharmaceutically and clinically relevant targets in MQC-associated brain disorders.